Characterization and Formulation of Butterfly Pea Flower Drinks (Clitoria ternatea L.) Fermented by Pineapple Peel based on Organoleptic Attributes and Gen-Z Acceptance - Muhammad Rizza Pahlevi; Hani Widhianata; Hesti Kurniahu (Universitas Labuhanbatu, 2025)
Background: Butterfly pea flowers (BPF) Clitoria ternatea were known as an antioxidant-rich functional drink ingredient at approximately 6.58 ppm. Various kinds of BPF drinks formulations had been consumed by the public, especially the older generation, due to their benefits. Meanwhile, the younger generation (Generation Z) was not familiar with these drinks and tended to enjoy soft drinks with sweet and fizzy flavors. This study formulated BPF with fermented pineapple peel (FPP) as an alternative to soft drinks. Methodology: Based on the SNI 01-2346-2006 standard, a total of 34 untrained Generation Z panelists were used to test organoleptic attributes (color, flavor, aroma, and sensation) using the Check-All-That-Apply approach and the hedonic test 5-point scale approach for panelist acceptability. Five formulations were used: BPF without sugar (A), with 10% sugar (B), (FPP + 10% sugar) (C), (BPF + FPP + 10% sugar) (D), and (BPF + FPP + 20% sugar) (E). Results: Based on Kruskal-Wallis with the Mann-Whitney further test for all organoleptic attributes, there were significant differences; the preferred color was formulation A, the aroma acceptability was neutral for all formulations, the preferred flavor was formulation E with a strong sweet and sour flavor, and for the sensation, formulation A was not preferred. The overall rating assessment showed that formulation E had the highest score due to strong sweet-sour flavor. Formulation E became the favorite drink of the panelist. This formulation could be a consideration for functional BPF drink innovation, which is the novelty of this study as an alternative to soft drinks with the Generation Z market share. Contribution: This study contributes scientifically by demonstrating that the combination of antioxidant-rich butterfly pea flower and fermented pineapple peel can be formulated into a functional drink with sensory attributes acceptable to Generation Z, thus bridging traditional herbal drinks with modern consumer preferences